CVBEM for a system of second-order elliptic partial differential equations - Ang, W.T.; Park, Y.S. (Elsevier Ltd., 1998)
A boundary element method based on the Cauchy's integral formulae and the theory of complex hypersingular integrals is devised for the numerical solution of boundary value problems governed by a system of second-order elliptic partial differential equations• The elliptic system has applications in physical problems involving anisotropic media• © 1998 Elsevier Science Ltd. All rights reserved